1999
DOI: 10.1007/s004390050917
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and genomic characterization of the gene encoding diacylglycerol kinase γ ( DAGK3 ): assessment of its role in dominant optic atrophy ( OPA1 )

Abstract: The family of diacylglycerol kinases (DAGKs) is known to play an important role in signal transduction linked to phospholipid turnover. In the fruitfly Drosophila melanogaster, a human DAGK ortholog, DGK2, was shown to underlie the phenotype of the visual mutant retinal degeneration A (rdgA). Previously, the gene encoding a novel member of the human DAGK family, termed DAGK3, was cloned and demonstrated to be abundantly expressed in the human retina. Based on these findings we reasoned that DAGK3 might be an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Moreover, we found that five out of the 14 genes were certainly involved in the function of the camera eyes of humans and octopuses. For example, diacylglycerol kinase ␥, which is expressed in the rod outer segment of the retina, was found in humans and octopuses, but not in the invertebrates examined except octopus (Stohr et al 1999). For another example, dihydroxyacetonephosphate acyltransferase is the peroxisomal key enzyme of plasmalogen biosynthesis in eye-lens epithelial cells (Thai et al 1999).…”
Section: The Function Of Camera Eye-specific Genesmentioning
confidence: 99%
“…Moreover, we found that five out of the 14 genes were certainly involved in the function of the camera eyes of humans and octopuses. For example, diacylglycerol kinase ␥, which is expressed in the rod outer segment of the retina, was found in humans and octopuses, but not in the invertebrates examined except octopus (Stohr et al 1999). For another example, dihydroxyacetonephosphate acyltransferase is the peroxisomal key enzyme of plasmalogen biosynthesis in eye-lens epithelial cells (Thai et al 1999).…”
Section: The Function Of Camera Eye-specific Genesmentioning
confidence: 99%
“…For mutational analysis, amplification of each of 24 exons of DAGK3 gene was conducted using PCR primer sets as reported previously (14). Direct sequencing was conducted in a conventional manner.…”
Section: Methodsmentioning
confidence: 99%
“…In this region, genes which have some impact on signal transduction are located, e.g. the diacylglycerol kinase 3 (DAGK3) gene, the PIKCA3 gene, and cytokins like the thrombopoietin gene [38, 39, 40, 41]. Furthermore, overrepresentations on 3q27–28 are common cytogenetic findings in severe dysplasias/carcinoma in situ, which may be a key event occurring early during carcinogenesis [42, 43].…”
Section: Discussionmentioning
confidence: 99%